Effect of light intensity and wavelength on nitrogen and phosphate removal from municipal wastewater by microalgae under semi-batch cultivation. Issue 9 (16th April 2022) - Bahman, Mahsa; Aghanoori, Marjan; Jalili, Hasan; Bozorg, Ali; Danaee, Soroosh; Bidhendi, Mehdi Esmaeili; Amrane, Abdeltif
ABSTRACT: Domestic, agricultural and industrial water activities lead to organic and inorganic pollution of the environment. Biotreatment of municipal wastewater with the potential production of biomass is a valuable feature of microalgae. In this study we evaluated the effects of wavelength and light intensity on phosphate and ammonium removal on the one hand, and biomass and protein production on the other hand by Spirulina platensis in municipal wastewater treatment under semi batch cultivation. S. platensis was inoculated at 40% in artificial wastewater open pond system. Red, blue and purple light with 3800, 4800 and 5800 lux light intensity under 12 h light and 12 h darkness were investigated. Cultivation was conducted in semi-batch conditions; after four days cultivation, one third of the culture was replaced with fresh medium. The highest biomass and protein concentrations were observed under blue light at 5800 lux light intensity, 5.45 and 3 g/l respectively cumulatively; while the highest amount of phosphate and ammonium removal were about 145 and 218 mg/l under purple light at 5800 lux intensity, respectively. The amounts of biomass and protein produced, as well as phosphate and ammonium removed, are therefore impacted by wavelength, light intensity, results show that light intensity and wavelength can be customized to reach on the one hand the highest biomass and protein production, and on the other hand to maximize the removal of phosphorous and ammonium. GRAPHICAL ABSTRACT: UF0001